(untitled) (Journal of Educational Sciences, 2022)
We know that the dynamic development of the country’s economy directly depends on the education system. The knowledge acquired by a student during traditional training is memorized, used rationally somewhere, but, in essence, is not used effectively by students in life. And in a modern developed society, knowledge is not enough for a citizen, it is important to be able to effectively apply the acquired knowledge in everyday life situations. Therefore, priority is now given to improving functional literacy, critical thinking and creativity of students. That is why the main goal of the implementation of the criteria assessment system is to improve the quality of education at school. This article discusses the introduction of a system of criteria assessment in the system of Kazakh education and the features of the creation and application of didactic materials in geography lessons, which are created using an online service. LearningApps.org and presents personal practical experience of using information technology tools in geography lessons with the help of this website and the analysis of teaching effectiveness. The purpose of the interactive module research LearningApps.org This is the development of individual creative skills of students in the information environment of the modern world during the educational process. In order to see the effectiveness of using the online service LearningApps.org an experiment and a survey of students in grades 7-10 were conducted in the training. As a result of the experiment , it turned out that when using an online service LearningApps.org in geography lessons, there was a noticeable improvement in the quality of knowledge at different stages of lesson. Key words: education, updated curriculum, criterion assessment, formative assessment, summative assessment, geography, information technology, service application LearningApps.org.